Age of the Taishu Group, southwestern Japan, and implications for the origin and evolution of the Japan Sea. (30th July 2014) - Ninomiya, Takashi; Shimoyama, Shoichi; Watanabe, Koichiro; Horie, Kenji; Dunkley, Daniel J.; Shiraishi, Kazuyuki
Abstract The Taishu Group, a marine formation with a thickness of >5400 m, crops out on Tsushima Island, located in the southwestern Japan Sea. The group, which is generally regarded as early Eocene to early Miocene in age, provides important information about the tectonic setting of the Japan Sea. In this study, we present new SHRIMP U–Pb dates for igneous zircons from the Kunehama Tuff, which is in the basal part of the Taishu Group, and the Oobaura Tuff, which is in the uppermost part of the group. Results show that the Taishu Group was deposited rapidly, during the short interval of 17.9–15.9 Ma (early–middle Miocene), and is equivalent to other early–middle Miocene strata found in the Japan Sea region. Our results provide new constraints on the geological history of the Japan Sea and its islands.